Political behaviour in organizations: a thai perspective - Ractham, Arun
The article studies 1. the concept of political behaviour in organizations in general, 2. political power within an organization, 3. low a state of neutrality within an organization in maintained 4. the relationship between political behaviour in an organization and process of decision-making, including individual interest in and withdrawal from organizational political behaviour, and 5. how an organizational administrator understands and manages political behaviour within his organisation. To minimize too much organization politics, the author appeals to those concerned that they stick with the merit system and for them to refrain from playing too much politics in order to enhance their political power
Keywords: Thailand; Politics; Organisational Behaviour; Organizational Behaviour - Thailand